The association of muscle and tendon elasticity with passive joint stiffness: In vivo measurements using ultrasound shear wave elastography - Chino, Kentaro; Takahashi, Hideyuki (Clinical biomechanics (Bristol), 2015)
Passive joint stiffness is associated with various tissues, including muscles, tendons, ligaments, and joint capsules. The specific elasticity of muscles or tendons can be measured using ultrasound shear wave elastography. To examine the association of muscle and tendon elasticity with passive joint stiffness, in vivo measurements of muscle and tendon elasticity were performed using ultrasound shear wave elastography. In 25 subjects, passive ankle joint stiffness was determined using the joint angle–passive torque relationship. The stiffness index of the muscle belly of the medial gastrocnemius (MG)—influenced by the muscle fascicles, its aponeuroses, and the proximal tendon—was quantified by the displacement of the muscle-tendon junction, which was visualized using B-mode ultrasonography during passive dorsiflexion. The stiffness index of the Achilles tendon—influenced by the tendon and the ligaments and joint capsule of the ankle—was similarly determined. The MG and Achilles tendon elasticity was measured using ultrasound shear wave elastography. Simple regression indicated a significant correlation between passive joint stiffness and stiffness index of the MG muscle belly (r=0.80) and Achilles tendon (r=0.60), but no correlation with elasticity of the MG (r=−0.37) or Achilles tendon (r=−0.39). Individual variations in the elasticity of either the MG or Achilles tendon are not associated with variations in passive ankle joint stiffness; however, variations in the elasticity of other tissues, including MG aponeuroses or the ligaments and joint capsule of the ankle, would be associated with the variations in joint stiffness. •Association of tissue elasticity with passive ankle joint stiffness was examined.•Passive joint stiffness was determined by the joint angle–torque relationship.•Tissue elasticity of muscles and tendons was measured by shear wave elastography.•Muscle and tendon elasticity did not correlate significantly with joint stiffness.•Muscle/tendon elasticity does not explain individual joint stiffness variations.